(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study evaluate the ethical concerns in the application of AI in business education programme in public universities in Cross River State. Three specific objectives, research questions and null hypotheses guided the study. Descriptive survey design was adopted in the study. The population comprised 52 business educators (males 30 and females 22) in two public universities in Cross River State: Unical and Uncross. The entire population was used since the size is manageable. Self-designed questionnaire title: Ethical Concerns in AI Application Scale was used to collect data from the respondents. The instrument was face validated by three subject experts and was tested for reliability using Cronbach Alpha which produced a coefficient of 0.86. Fifty-two (52) copies of the instruments were administered and were all collected after completion. Mean and Standard Deviation were used to answer the research question while t-test was used to test the hypotheses at 0.05 level of significance. Findings indicated that accountability, privacy and bias are of great concern in the application of AI in business education programme. Furthermore, institution, age and gender of business educators were not significant in respect to the extent of accountability, privacy and gender concerns in the application of AI in business education programme in public universities in Cross River State. It was recommended among others that governments should implement regulations to ensure that AI systems adhere to strict privacy standards and developers are held accountable for any breaches.